Study to Assess the Effectiveness of STP on Risk Factors and Prevention of Peptic Ulcer - Eswarappa.S; K Ramu; I.Clement, (Research & Review: Management of Emergency and Trauma Nursing (e-ISSN: 2582-0494), 2019)
The stomach is very important component of digestive system it is an enlarged segment of the digestive tract which is present in the left superior part of the abdomen. Stomach shape and size vary from person to person even within the same individual its size and shape change from time to time which depends on its food content and the posture of the body. In India Peptic Ulcer Disease. According to the latest WHO data published in 2017 Peptic Ulcer Disease Deaths in India reached 57,658 or 0.66% of total deaths. The age adjusted Death Rate is 5.79 per 100,000 of population ranks India #53 in the world. A study to assess the effectiveness of structured teaching program on risk factors and prevention of peptic ulcer among middle age population between the age group of 30-50years in selected rural areas at Tumkur District was conducted in partial fulfillment of the requirement of the degree of Master of Science in Nursing at Sri Ramana Maharshi college of Nursing, Tumkur. The study objectives are: 1. To assess the existing knowledge on risk factors and prevention of peptic ulcer among middle age population. 2. To determine the effectiveness of structured teaching program on risk factors and prevention of peptic ulcer among middle age population. 3. To determine the difference between pre-test and post-test knowledge scores on risk factors and prevention of peptic ulcer among middle age population. 4. To find out the association between posttest knowledge level with their selected demographic variables. Research Design: Quasi experimental in one group pretest and posttest design was adopted to evaluate the effectiveness of risk factors and prevention of peptic ulcer Results: There will be significant difference between mean pre-test knowledge score and post-test knowledge scores among middle age population on risk factors and prevention of peptic ulcer. Table depicts mean percentage of pretest, posttest and enhanced Knowledge scores of respondents in different aspects of care of clients with Traction. In aspect ‘Knowledge regarding peptic ulcer’, mean percentage of knowledge score in pre-test was 39.66% and in post-test was 81.33% with enhancement of 41.66%. The calculated paired ‘t’ test value was 16.02 which was found to be significant. In aspect ‘Knowledge regarding risk factors and prevention of Peptic ulcer’, mean percentage of knowledge score in pre-test was 40.33% and in post-test was 81.88% with enhancement of 41.66%. The calculated paired ‘t’ test value was 12.5 which was found to be significant. All the calculated ‘t’ values were significant at 0.05% level of significance. Hence stated null hypothesis H01 is rejected in relation to all aspects of knowledge and research hypothesis H1 is accepted. Interpretations and Conclusion: The finding of the study to help the professional nurses and sudden to develop the inquiry by providing a baseline. The general aspects of the study results can be made by further replication of the study. This study help the nurse researchers to develop in depth in to the development of teaching module and set information of clients with peptic ulcer towards the promotion of healthy life and prevent of complication.